Tom Clancy's Op-center War of eagles - Rovin, Jeff; Clancy, Tom 1947-; Pieczenik, Steve R; Copyright Paperback Collection (Library of Congress) (New York Berkley Books, 2005)
When a mysterious cabal within the U.S. State Department causes tensions to erupt between Iran and Azerbaijan and plots to depose the President of the United States, Paul Hood and the Op-Center team must stop the conspiracy
1
Keywords: Adventure fiction